The fundamental principles of full-sized technology for check on strength a new point equipment - Moiseenko, K. V. (Science and Transport Progress, 2011)
The conditions, which are necessary for full-scale test of a switch on strength, purpose and tasks of tests, requirements to laying, operation and state before and during tests are described; the scheme of installation of devices, the basic requirements to measuring tools and formation of a test train, the principles of data processing and experimental data analysis are presented.